Fast and Accurate Determination of the Singlet–Triplet Gap in Donor–Acceptor and Multiresonance TADF Molecules by Using Hole–Hole Tamm–Dancoff Approximated Density Functional Theory. Issue 8 (1st June 2022) - Woon, Kai‐Lin; Nikishau, Pavel A.; Sini, Gjergji
Abstract: One of the requirements to design efficient emitters based on the multiresonance (MR)‐ or donor–acceptor (D‐A) thermally activated delayed fluorescence (TADF) materials is a relatively small energy gap between the lowest singlet and triplet excited states (Δ E ST ). High‐level ab initio calculations of their Δ E ST provide benchmark results, but they are very time consuming and little practical for large‐size systems. Here, the performances of hole–hole Tamm–Dancoff approximated density functional theory (hh‐TDA‐DFT) and the functional dependent accuracy of hh‐TDA are examined on Δ E ST of a large number of MR‐ and D‐A TADF molecules. The results indicate that hh‐TDA combined with the hybrid functional B3LYP can predict Δ E ST values for a wide number of MR‐TADF molecules with mean absolute error (MAE) within 0.04 eV with correlation as high as 0.75. For D‐A TADF molecules, Δ E ST is less sensitive to the nature of the functionals, with MAE as low as 0.07 eV. The larger discrepancy between Δ E ST obtained from hh‐TDA‐DFT and experimental data in several oxygen‐containing MR‐TADF molecules is assumed to stem from the aggregation tendency of these compounds in solution. These findings provide important insights on the role of aggregation in reducing the Δ E ST of MR‐TADF compounds. Abstract : Hole–hole Tamm–Dancoff approximation with B3LYP functional can be used to accurately predict Δ E ST . By using this method, microaggregates of multiresonance thermally activated delayed fluorescence compounds are found to reduce the Δ E ST as compared to the monomers.